Uji Aktivitas Antibakter Formulasi Sediaan Salep Ekstrak Daun Bidara (Ziziphus mauritania) terhadap Bakteri Staphylococcus aureus - shindi pratiwi putri; Al Syahril Samsi; Israini Suriati (Jurusan Farmasi Universitas Negeri Gorontalo, 2023)
Infectious diseases are the highest contributor to morbidity and mortality in developing countries, including Indonesia. This is inseparable from the many pathogenic bacteria that attack humans, causing various diseases. Infection due to Staphylococcus aureus, starting from the entry of bacteria through a wound scratch. Infection will be characterized by tissue damage accompanied by local abscesses such as boils or pimples. As an effort to prevent Staphylococcus aureus bacterial infection, antibacterial ointment preparations are needed that can prevent infection and are practical in their use. In this study, the antibacterial activity test of the ointment formulation of Bidara leaf extract (Ziziphus mauritania) was carried out with concentrations of 40%, 50% and 60% w/v. the test bacteria used was Staphylococcus aureus. This research was conducted using the agar diffusion method. The results showed that the test results for antibacterial ointment preparations with Bidara leaf extract with concentrations of 40%, 50% and 60% w/v fulfilled the results of the organoleptic evaluation test, homogeneity, spreadability test, adhesion test and pH test. The results of the ANOVA analysis showed that the formulation of Bidara leaf extract ointment (Zizyphus mauritania) with a concentration of 50% and 60% w/v had non-significant antibacterial activity with gentamicin sulfate ointment as a positive control against the growth of Staphylococcus aureus bacteria.